PENGEMBANGAN SMART MINI TRAINER SISTEM KELISTRIKAN BODI OTOMOTIF BERBASIS IOT UNTUK MENDUKUNG PEMBELAJARAN ERA INDUSTRI 4.0 - Sukardi Sukardi; Muhammad Hudan Rahmat; Agung Samudra; Sri Murwantini; Harie Setiyadi Jaya (Steam Engineering, 2026)
Automotive Electrical Systems learning faces the constraints of the availability of expensive, static, and digital data visualization practice media. This condition hinders the understanding of digital data-based damage diagnosis which is now a requirement of industry 4.0. This study aims to: (1) develop a valid smart mini trainer; (2) test the effectiveness of the smart mini trainer on the understanding of the concept of digital data-based damage diagnosis and student motivation; and (3) analyze the development cost efficiency between the smart mini trainer and the standard trainer. The research method uses the instructional development institute (IDI) research and development model with 30 students as trial subjects. The expert validation results show that the smart mini trainer is very feasible/valid (0.93) for use in learning. The trial results show that 83.3% of students are motivated to learn the smart mini trainer. In addition, the media interface design is considered user-friendly, as evidenced by the total accumulation of positive responses reaching 66.6%. The cost efficiency analysis shows that substituting mini variant components can save costs between 60% and 98% compared to the standard trainer. The implications of this research offer a low-cost, portable and valid learning media solution for training digital data-based diagnostic logic in Automotive Electrical Systems.